Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/onc.2017.21
|View full text |Cite|
|
Sign up to set email alerts
|

DUB3 and USP7 de-ubiquitinating enzymes control replication inhibitor Geminin: molecular characterization and associations with breast cancer

Abstract: Correct control of DNA replication is crucial to maintain genomic stability in dividing cells. Inappropriate re-licensing of replicated origins is associated with chromosomal instability (CIN), a hallmark of cancer progression that at the same time provides potential opportunities for therapeutic intervention. Geminin is a critical inhibitor of the DNA replication licensing factor Cdt1. To properly achieve its functions, Geminin levels are tightly regulated through the cell cycle by ubiquitin-dependent proteas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 52 publications
3
62
0
Order By: Relevance
“…Tumour cell percentage staining was subsequently stratified as either >75% or <75%, as this adequately described the positive cases. IHC analysis was performed for the markers, the results for some of which have been published previously . The cut‐off value for HER2 positivity was based on a silver in‐situ hybridisation (SISH) score of >6 and an IHC score of 3+ if SISH was unsuccessful.…”
Section: Methodsmentioning
confidence: 99%
“…Tumour cell percentage staining was subsequently stratified as either >75% or <75%, as this adequately described the positive cases. IHC analysis was performed for the markers, the results for some of which have been published previously . The cut‐off value for HER2 positivity was based on a silver in‐situ hybridisation (SISH) score of >6 and an IHC score of 3+ if SISH was unsuccessful.…”
Section: Methodsmentioning
confidence: 99%
“…USP7 is also a regulator of cell cycle protein Geminin. Lack of Geminin can cause re‐replication events ultimately leading to genome instability . It is proposed that USP7 can be targeted for treatment of haematological malignancies with DDR defects .…”
Section: Ubiquitin Specific Protease 7 (Usp7)mentioning
confidence: 99%
“…Lack of Geminin can cause re-replication events ultimately leading to genome instability. 76 It is proposed that USP7 can be targeted for treatment of haematological malignancies with DDR defects. 50 In case of CLL, USP7 inhibition prevents homologous recombination repair (HRR) and…”
Section: P53mentioning
confidence: 99%
“…They protect proteins from proteasomal degradation and it was suggested that their inhibition could promote the degradation of otherwise "undruggable" targets (Maertens et al, 2010;McClurg & Robson, 2015). Deregulation of the ubiquitination/deubiquitination PTM system was demonstrated to be associated with various disorders such as cancers (Glasser & Julian, 1986;Hernandez-Perez et al, 2017;Maertens et al, 2010;McClurg & Robson, 2015;Turnbull et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitin-specific protease 7 (USP7), otherwise known as herpesvirus-associated ubiquitin-specific protease 7 (HAUSP), is a 135 kDa protein and a member of the DUB family, which functions in regulating protein stability and localization (Hussain et al, 2009). It plays a critical role in vital intracellular processes such as epigenetic regulation, cell cycle regulation, cell growth and survival (Gallo & Dirks, 2016;Glasser & Julian, 1986;Hernandez-Perez et al, 2017;Ma & Yu, 2016;Roby et al, 1993). Of note, its role in stabilizing various tumor suppressors, such as p53, Mdm2, PTEN and Myc (Castracane & Jordan, 1975;He et al, 2014;Hernandez-Perez et al, 2017;Hussain et al, 2009;Ma & Yu, 2016;Roby et al, 1993), has been well-characterized and its upregulation has been associated with many cancers (Hernandez-Perez et al, 2017;Jiang et al, 2016;Roby et al, 1993;Turnbull et al, 2017).…”
Section: Introductionmentioning
confidence: 99%